Edukasi Peran Kepala Ruang dalam Menerapkan Gaya Kepemimpinan Caring Leadership - Wati, Ni Made Nopita; Dewi, Ni Luh Putu Thrisna; Lisnawati, Ketut; Sanjiwani, Anak Agung Sri; Sudarma, Nyoman (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2024)
Background: Leadership is one of the crucial aspects in managing a health care unit, especially in nursing. A leadership style that focuses on attention and empathy, or known as Caring Leadership, has been shown to improve the quality of service and patient satisfaction. This community service aims to improve the understanding and ability of the head of the room in implementing the Caring Leadership style. Methods: This activity is carried out through a series of training and interactive discussions involving the head of the room in various hospitals. Educational materials include an introduction to the concept of Caring Leadership, effective communication techniques, and strategies in supporting the nursing team. Results: The results of this activity show an increase in participants' knowledge and skills in applying Caring Leadership in their work environment. The impact is expected to create a more harmonious work atmosphere and support the improvement of the quality of health services. Conclusion: This activity also contributes to improving the welfare of the nursing team and patient satisfaction.